Against the flow : education, the arts and postmodern culture - Abbs, Peter, 1942- (RoutledgeFalmer, 2003)
This book calls for education to become an end in itself, as opposed to the means to an end, and for a place to be found in contemporary education for the spiritual, the aesthetic and the ethical.